The Effects of Nonuniform Illumination on the Electrical Performance of a Single Conventional Photovoltaic Cell - Damasen Ikwaba Paul; Mervyn Smyth; Aggelos Zacharopoulos; Jayanta Mondol (International Journal of Photoenergy)
Photovoltaic (PV) concentrators are a promising approach for lowering PV electricity costs in the near future. However, most of the concentrators that are currently used for PV applications yield nonuniform flux profiles on the surface of a PV module which in turn reduces its electrical performance if the cells are serially connected. One way of overcoming this effect is the use of PV modules with isolated cells so that each cell generates current that is proportional to the energy flux absorbed. However, there are some cases where nonuniform illumination also exists in a single cell in an isolated cells PV module. This paper systematically studied the effect of nonuniform illumination on various cell performance parameters of a single monocrystalline standard PV cell at low and medium energy concentration ratios. Furthermore, the effect of orientation, size, and geometrical shapes of nonuniform illumination was also investigated. It was found that the effect of nonuniform illumination on various PV cell performance parameters of a single standard PV cell becomes noticeable at medium energy flux concentration whilst the location, size, and geometrical shape of nonuniform illumination have no effect on the performance parameters of the cell.